MEDIASI INDONESIA DALAM PROSES PERDAMAIAN PALESTINA- ISRAEL - Wardoyo, Broto; Wirawan, Hariyadi; Santiko, Utaryo (UI Scholars Hub, 2011)
The aim of this research is to build a strategy for Indonesia’s involvement in the Palestinian- Israeli peace process. We first identify the main obstacle for such involvement, which, in our view, is the absence of official contacts between Indonesia and Israel The opening of such contacts, however, is not possible due to a number of reasons. First and foremost, the opening of such contacts will create tremendous political pressures to the government from the Islamic communities. In addition, the economic gains of such an opening are not quite tangible. Finally, the opening of such contacts could easily be interpreted as a violation to the constitution which clearly calls for the right to independence. To tackle those problems, our proposal is to build an unofficial-official which combine the Taiwan model and the backchannel model and add it with the normative framework and pragmatic interests for Indonesia’s involvement.